Project-based learning in biotechnology: A profile of senior high school students’ 21st-century 4Cs in South Labuhanbatu Regency - Hasmi Syahputra Harahap; Sri Rahayu Lestari; Ibrohim Ibrohim; Sofia Ery Rahayu (Jurnal Biolokus : Jurnal Penelitian Pendidikan Biologi dan Biologi, 2026)
Twenty-first-century education requires students to develop critical thinking, creativity, collaboration, and communication (4Cs) to address increasingly complex scientific and societal challenges. This study aimed to profile senior high school students’ 21st-century skills in South Labuhanbatu Regency, North Sumatra, through the implementation of Project-Based Learning (PjBL) in biotechnology instruction. A descriptive cross-sectional survey design was employed involving 157 twelfth-grade students. Data were collected through self-assessment questionnaires, peer-assessment questionnaires, observation rubrics, and documentation of PjBL activities. Descriptive statistical analysis was used to examine students’ 4Cs. The findings revealed that the overall mean score of students’ 4Cs was 67.33, indicating a moderate level of proficiency. Self-assessment results showed mean scores of 67.73 for critical thinking, 64.25 for creativity, 65.76 for collaboration, and 67.74 for communication. Similarly, peer-assessment results indicated mean scores of 66.07, 64.34, 74.87, and 67.91 for critical thinking, creativity, collaboration, and communication, respectively, all within the moderate category. Collaboration achieved the highest score, particularly in peer assessment, whereas creativity consistently obtained the lowest score across both assessment methods. The consistency between self- and peer-assessment results suggests that collaboration and communication were the most developed competencies among students. Although variations in students’ skill profiles may be influenced by pedagogical, contextual, and social factors, the findings were obtained from biotechnology learning activities implemented through PjBL involving investigation, discussion, problem-solving, and scientific presentation. These findings describe students’ 21st-century skill levels in a PjBL-based biotechnology learning context and provide empirical information that may inform future instructional strategies aimed at supporting 4C development.